Extracellular Aspects on N-Metyl-D-Aspartate (Nmda) Glutamate Receptor in Schizophrenia - Zelaya Castro, Pío (1999)
OBJECTIVE: To determine the relationship between extracellular levels of pH, Ca2+ and Mg2+ and schizophrenia, regarding the glutamate N-metyl-D-Aspartate (NMDA) receptor-hypofunction theory as primary mechanism in the etiology of schizophrenia. MATERIAL AND METHODS: Cerebrospinal fluid (CSF) pH, Ca2+ and Mg2+ levels were measured in 10 schizophrenic inpatients with antipsychotic treatment diagnosed according to the ICD-10, at the Hospital Rebagliati Mental Health Department in Lima, Peru, and 7 non psychiatric patients. RESULTS: pH levels from schizophrenic group (6,95 ± 0,06) wese significantly lower than control group ones (7,30 ± 0,12) (difference: 0,35 units) (p <0,005). Ca2+ levels were 0,14 mg/dL lower in schizophrenic group (4,44 ± 0,47 mg/dL) than in control group (4,58 ± 0,21 mg/dL) (p >0,05). Mg2+ leves were also lower in the schizophrenic group (1,61 ± 0,67 mg/dL) compared with control group (1,58 ± 0,26 mg/dL) (difference: 0,03 mg/dL, p >0,05). CONCLUSIONS: These findings suggest that diminished pH in schizophrenic patients CSF may be one of the mechanisms involved in the NMDA receptor-hypofunction described in schizophrenia.